Cumulative socio‐contextual risk and child abuse potential in parents of young children: Can social support buffer the impact?. Issue 4 (10th June 2020) - McGoron, Lucy; Riley, Moira R.; Scaramella, Laura V.
Abstract: Child abuse potential refers to characteristics and practices closely linked to child abuse. Past investigations document that the number of risk factors parents experience is a correlate of child abuse potential. The purpose of this investigation was to test a model with multiple domains of risk including cumulative socio‐contextual risk, parenting locus of control, children's externalizing behaviour problems, social support, and child abuse potential. Using self‐report data from 87 mothers of children between the ages of 1 and 5 years old, bivariate correlations and linear regression analyses revealed that cumulative socio‐contextual risk was positively associated with child abuse potential and that this association remained statistically significant when controlling for parenting locus of control and child externalizing behaviour problems. Additionally, social support moderated the association between cumulative risk and child abuse potential.